Quoting and retweeting as communicative practices in computer mediated discourse. (December 2017) - Gruber, Helmut
Abstract: In this paper, quoting in e-mail communication and retweeting in Twitter message streams is analysed as users' recontextualization practices which share formal features but serve different communicative needs. After a short discussion of user related push factors and medium specific pull factors and their interplay in computer mediated discourse, quoting in e-mail discussions is characterised as a CMD practice through which users manage interactional and topical coherence problems caused by technological factors. Retweeting, conversely, is characterised as a platform-specific variant of "sharing" digital objects which is afforded through social network sites. A formal and functional analysis of edited and unedited retweets reveals that this recontextualization practice shares formal properties with quoting but that it is mainly used for interpersonal rather than for topic- and interaction-oriented ends. The results lay the basis for some generalisations concerning the conceptualization and the interplay of communicative push and pull factors in current accounts of the adaptation of existing and the emergence of new social practices and genres in CMD.